A migration case of Kii amyotrophic lateral sclerosis/parkinsonism dementia complex with the shortest stay in the endemic area and the longest incubation to develop the disease. (December 2017) - Tsunoda, Keiichiro; Yamashita, Toru; Shimada, Hitoshi; Nomura, Emi; Takahashi, Yoshiaki; Shang, Jingwei; Sato, Kota; Takemoto, Mami; Hishikawa, Nozomi; Ohta, Yasuyuki; Higuchi, Makoto; Suhara, Tetsuya; et al.
Highlights: A migration case of Kii ALS/PDC with the shortest stay in the endemic area and the longest incubation to develop the disease. This case suggests a genetic factor for the disease development. This is the first case report of tau imaging of Kii ALS/PDC. Abstract: Amyotrophic lateral sclerosis/parkinsonism dementia complex (ALS/PDC) is an endemic disease observed in the Kii peninsula, Guam, and Papua. We report a case of a 76-year old man with ALS/PDC of the Kii peninsula of Japan (Kii ALS/PDC). The patient was born and grew up in the Kii peninsula. He moved out at age three, and developed symptoms 73 years later. He showed pyramidal sign, parkinsonian symptoms, and mildly impaired cognitive function. 131 I-metaiodobenzylguanidine myocardial scintigraphy showed decreased cardiac sympathetic nerve function, and dopamine transporter single photon emission computed tomography imaging showed decreased 123 I-N-ω-fluoropropyl-2β-carbomethoxy3β-(4-iodophenyl) nortropane accumulation. Cerebral blood flow showed hypoperfusion. Positron emission tomography showed widespread tau deposition in his brain. This is a migration case of Kii ALS/PDC with the shortest stay in the endemic area and the longest delay to develop the disease, indicating a genetic factor for the disease development in a considerable degree.